Identification of Periopathogenes from Dental Plaque in Periodontal Patients with PCR Technique and Their Association with Composite Interleukin-1 Genotype - Stojanovska, Aneta Atanasovska; Todoroska, Saska; Popovska, Mirjana; Muratovska, Ilijana; Bedzeti, Linda Zendeli (Prilozi (Makedonska akademija na naukite i umetnostite. Oddelenie za medicinski nauki), 2019)
The present study aimed to assess the presence of main types of microorganisms involved in the aetiopathogenesis of chronic periodontitis with PCR technique and determinates the presence of composite IL-1 genotype and their associations with founded bacteria. The examined group was consisted from 20 subjects with diagnosed chronic periodontitis and 20 healthy control without periodontitis. Clinical parameters like gingival index (GI), plaque index (PI), bleeding on probing (BOP), periodontal pocket depth (PPD) and clinical attachment lost (CAL) were determinates. Subgingival dental plaque was collected using a sterilized paper point. We used Parodontose Plus test, reverse hybridization kit, for the detection of periodontal marker bacteria, as well as for the detection of composite Interleukin -1 Genotype Results: The most present bacterial species detected from subgingival dental plaque was Treponema denticola and Porfiromonas gingivalis which was present in 65% of examined patients. In relation to the presence of positive genotype in patients, there was no significant difference between the test and control group for p> 0.05 (p = 1.00). For χ2=8,17 (p=0,06, p<0,05) there is an association between Prevotella intermedia, and composite genotype. Between positive genotype and analyzed bacterial species A. actinomycetem comitans for p> 0.05 (p = 1.00), P. gingivalis for p> 0.05 (p = 0.16), T. Forsythia for p> 0.05 (p = 0.20), T. Denticola for p> 0.05 (p = 0.64) no association was found. This investigations confirmed the strong association of these five examined periopathogenes with periodontitis.